Finger Painting to Improve Fine Motor Skills of early Age Children - Kalamak, Jeni Tonda; Danga, Sriyanti Yaku; Sari, Nia Rahma (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2023)
This study aims to improve children's fine motor skills through finger painting activities in Group B at Rehoboth Christian Kindergarten, Central Sumba. This research is a type of Classroom Action Research with a collaborative method. The subjects of this study were children in Group B 5-6 years. The data collection technique is observation (checklist). The research instrument is an observation sheet. Data analysis techniques using descriptive qualitative and quantitative. This classroom action research was carried out in two cycles. The results of the research show that the fine motor component can be improved using finger painting activities. In the pre-action research action, the children who were said to have completed reached 15.46%, in the first cycle the children who were completed reached 72% and in the second cycle, the children who were completed reached 95% were said to be in very good criteria. So it can be said that the children's fine motor skills after being given treatment increased with finger painting activities.